Effect of springback on A6061 sheet metal bending: a review - Cinar, Zeki; Mohammed Asmael,; Zeeshan, Qasim; Safaei, Babak (Penerbit Universiti Kebangsaan Malaysia, 2021)
Springback is defined as undesirable shape change that occurs after forming process upon unloading due to the occurrence of elastic recovery of the part. Aluminum alloy with high content of magnesium such as A6061 is preferred for high formability limit to be used in automotive industry. However, generally springback turns out to be a drawback. Many researchers have examined the springback of A6061 by considering parameters such as bent angle, die shoulder radius, blank holder force, sheet thickness, punch thickness, modulus young, yield strength, Poisson’s ratio, annealing temperature, applied load and bending operations such as V bending, deep drawing, tube bending, 3 point bending, U bending, and wipe bending. In this research, a comprehensive review is carried out to investigate process parameters and bending operations having critical impact on springback of A6061 and publications in the literature based on springback effect for A6061 studied in order to observe the number of publications by authors and the number of publications by affiliation. It is observed that sheet thickness and bent angle parameters have substantial effect on the springback. V bending and deep drawing are the commonly used bending processes. In addition, a critical contribution is presented by considering process parameters and analysis methods in order to provide a guidance for researchers for further research studies.